(untitled) (Simbiótica. Revista Eletrônica, 2023)
Agriculture passed through a process of industrialization, which incorporated industrial characteristics into food production. This had positive aspects but had environmental impacts and economic and productive dependence on corporations. However, concerns about climate change have led some farmers to adopt the conventional sustainable system, aimed at organic agriculture, but supported by certification seals, or fair-trade systems aimed exportations. While agroecology poses questions about food supply and distribution, access to income, land, seeds and other resources. In the three situations there are different interpretations about the use of the planet’s resources. Therefore, the objective is to analyze the use of land system resources, in relation to three agricultural production systems: conventional (green revolution), sustainable conventional and agroecology.